Adverse Health Effects and Unhealthy Behaviors among Medical Students Using Facebook - Sami Abdo Radman Al-Dubai; Kurubaran Ganasegeran; Mustafa Ahmed Mahdi Al-Shagga; Hematram Yadav; John T. Arokiasamy (The Scientific World Journal)
Little is known about the relationships between adverse health effects and unhealthy behaviors among medical students using Facebook. The aim of this study was to determine the associations between adverse health effects and unhealthy behaviors with Facebook use. A cross-sectional study was conducted in a private university in Malaysia among 316 medical students. A self-administered questionnaire was used. It included questions on sociodemographics, pattern of Facebook use, social relationship, unhealthy behaviors, and health effects. Mean age was 20.5 (±2.7) years. All students had a Facebook account. The average daily Facebook surfing hours were 2.5 (±1.7). Significant associations were found between average hours of Facebook surfing and the following factors: isolation from family members and community, refusing to answer calls, musculoskeletal pain, headache, and eye irritation (P<0.005). The average hours spent on Facebook were significantly associated with holding urination and defecation while online, surfing Facebook until midnight, and postponing, forgetting, or skipping meals (P<0.005). The average hours spent on Facebook were associated with adverse health effects and unhealthy behaviors among medical students, as well as social isolation from the family and community.